Perkawinan Nyentana di Bali: Urgensi, Tata Cara, dan Prospeknya di Era Modern - I Wayan Bhayu Eka Pratama; Ni Nengah Dhea Riska Putri Nandita; Ni Nyoman Indah Ratnasari (CV Rewang Rencang, 2021)
Nyentana's marriage was a deviation from the patrilineal kinship system in Bali. The implementation of this marriage aims to continue the lineage of a family that does not have a son. The implementation of Nyentana Marriage relates to the procession of the adoption of girls to be Sentana Rajeg in order to be entitled to continue the descendants of her family. Nyentana marriage is often avoided by men because of the difficulty of obtaining parental blessings, inheritance conflicts, and the urge for adaptation to new environments. This issue gave rise to the alternative marriage of Pada Gelahang. Pada Gelahang's Mating System positions the position between male and female equal as purusa. As a result, the responsibilities of men and women in their original families are equally as important as that of a head of the family.